2012
DOI: 10.1002/ajh.22241
|View full text |Cite
|
Sign up to set email alerts
|

Blood tests may predict early primary myelofibrosis in patients presenting with essential thrombocythemia

Abstract: According to World Health Organization (WHO)-defined criteria, patients presenting clinically as essential thrombocythemia (ET) may show early primary myelofibrosis (PMF) with accompanying thrombocythemia [1]. Previous clinicopathological studies revealed that laboratory parameters like gender-matched hemoglobin (Hb), white blood cell (WBC) count, and particularly lactate dehydrogenase (LDH) values are significantly different in PMF [2]. By strictly applying the WHO criteria, our investigation was aimed to stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 116 publications
1
30
0
Order By: Relevance
“…As a result, some cases of early-primary myelofibrosis (early-PMF) could have been included in the analysis. However, the strict distinction between ET and early-PMF is not of pivotal importance when looking for thrombotic risk factors, since the incidence of thrombosis has been reported to be comparable in these two clinical entities [23,24]. Moreover, the histological discrimination between ET and early-PMF is not always easy to assess and reproducible, particularly in peripheral Centers without a specific expertise on MPNs histology; therefore, exploring additional risk factors for thrombosis in these patients is of utmost relevance for everyday clinical management.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, some cases of early-primary myelofibrosis (early-PMF) could have been included in the analysis. However, the strict distinction between ET and early-PMF is not of pivotal importance when looking for thrombotic risk factors, since the incidence of thrombosis has been reported to be comparable in these two clinical entities [23,24]. Moreover, the histological discrimination between ET and early-PMF is not always easy to assess and reproducible, particularly in peripheral Centers without a specific expertise on MPNs histology; therefore, exploring additional risk factors for thrombosis in these patients is of utmost relevance for everyday clinical management.…”
Section: Discussionmentioning
confidence: 99%
“…6,[25][26][27] However, little data are available on selected cohorts of young individuals with an ET/early-PMF diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…This study was extremely original and innovative since, in spite of the recent widening of the off-label indications in pediatric [20,21,27,28] and adult [19] patients, no randomized, placebo-controlled trial in critically ill pediatric or adult patients has ever investigated clinically relevant endpoints. Another unique feature of our trial is that it enrolled patients admitted to the ICU for a primary disorder other than sepsis (mostly cardiac pathology or acute lung failure).…”
Section: Key Findingsmentioning
confidence: 99%
“…No bleeding complications related to the study drug were reported, and most studies underlined normalization of inflammatory markers and of coagulation abnormalities. Notably, recent case reports suggest that the use of protein C zymogen is widespread in in other clinical settings such as adult solid tumors, oncohematology, and pediatric amputations [19,20,27].…”
Section: Previous Relevant Studiesmentioning
confidence: 99%
See 1 more Smart Citation